Shifting the Balance: How Top-Down and Bottom-Up Input Modulate Pain via the Rostral Ventromedial Medulla - Chen, Qiliang; Heinricher, Mary M. (Frontiers in Pain Research, 2022)
The sensory experience of pain depends not only on the transmission of noxious information (nociception), but on the state of the body in a biological, psychological, and social milieu. A brainstem pain-modulating system with its output node in the rostral ventromedial medulla (RVM) can regulate the threshold and gain for nociceptive transmission. This review considers the current understanding of how RVM pain-modulating neurons, namely ON-cells and OFF-cells, are engaged by “top-down” cognitive and emotional factors, as well as by “bottom-up” sensory inputs, to enhance or suppress pain.